Sejarah dan Pengaruh Tradisi Takiran pada Masyarakat Desa Tugu Agung, Kecamatan Lempuing, Kabupaten Ogan Komering Ilir - Serli Wulandari; Adi Warsito; Indah Zulaikha (Local History & Heritage, 2023)
This paper discusses the role of cultural traditions, specifically the takiran tradition, in the Tugu Agung community. Using local history as a reference, this research aims to answer questions regarding the history and significance of the takiran tradition in Tugu Agung Village. Field research was conducted using the functionalism concept of Bronislaw K. Malinowski. In this study the authors used data collection techniques by direct observation and interviews. The method used is using qualitative methods with primary data sources through interviews with local leaders.The study found that the takiran tradition has two important aspects, religious and social. The religious aspect emphasizes the importance of fulfilling Islamic obligations, while the social aspect focuses on improving social interactions for better effectiveness and efficiency. This has resulted in the formation of a cohesive Tugu Agung community, capable of harmonious coexistence with their environment and fellow residents. The study highlights the significant role of cultural traditions in shaping communities and improving social interactions.